Evidence in Practice Award for UK Librarians - Editorial Team (Evidence Based Library and Information Practice, 2007)
The Second Evidence in Practice Award in conjunction with the Third UK Clinical Librarian Conference is now open for entries. We hope to bring together case studies that can be shared and used to persuade decision makers of the value of library and information services. The Second Evidence in Practice Award is sponsored by The National Library for Health and BMJ Group Clinical Evidence. It is open to any library & information professional in the UK who, working with health professionals, has made a difference in patient care. You may be working in any sector (e.g. primary or secondary care, consumer health information) and at any type of health organization (e.g. a professional body or a voluntary organization). Partnerships of information and health professionals are invited to enter the competition by providing a structured abstract, describing (in approximately 750 words) how health information provided by their library or information service has impacted patient care or service delivery. Entries can be submitted up to March 31,2007 after which anonymous case studies will be judged by an independent panel combining clinical and information expertise. The judges’ decision will be final. The winners will each receive a Personal Digital Assistant, financial support towards attendance at a professional conference or course of their choice, plus a free delegate place at the Third Clinical Librarian conference. The award will be presented at the Third UK Clinical Librarian Conference, 11th & 12th June 2007, St William's College, York Minster, where the award winners will have an opportunity to share their example of successful practice. For more details, follow the link from: http://www.uhl-library.nhs.uk/clinlibconf2007.htm or contact Linda Ward Library Services Manager University Hospitals of Leicester NHS Libraries Education Centre Library, LGH, Gwendolen Rd. LE5 4PW. Tel: 0116 2588124 Fax: 0116 2588078 Medical Library, GH, Groby Rd. LE3 9PQ. Tel: 0116 2502303 Fax: 0116 2563334 Email: linda.ward@uhl-tr.nhs.uk or lmw12@le.ac.uk Please take a short while to reflect on how you have made a difference and share it with your professional colleagues. On behalf of the EiP Award / CL conference team.